Osmotic Adjustment in Wheat (Triticum aestivum L.) During Pre- and Post-anthesis Drought - Verbeke, Sarah; Padilla-Díaz, Carmen María; Haesaert, Geert; Steppe, Kathy (Frontiers in Plant Science, 2022)
Pre-anthesis drought is expected to greatly increase yield losses in wheat (Triticum aestivum L.), one of the most important crops worldwide. Most studies investigate the effects of pre-anthesis drought only at maturity. The physiology of the plant before anthesis and how it is affected during drought is less studied. Our study focused on physiological patterns in wheat plants during pre- and post-anthesis drought. To this end, we measured leaf xylem water potential, osmotic potential and water content in different plant parts at a high temporal frequency: every three days, three times a day. The experiment started just before booting until two weeks after flowering. Drought stress was induced by withholding irrigation with rewatering upon turgor loss, which occurred once before and once after anthesis. The goal was to investigate the patterns of osmotic adjustment, when it is used for protection against drought, and if the strategy changes during the phenological development of the plant. Our data gave no indication of daily osmotic adjustment, but did show a delicate control of the osmotic potential during drought in both leavesand stem. Under high drought stress, osmotic potential decreased to avoid further water loss. Before anthesis, rewatering restored leaf water potential and osmotic potential quickly. After anthesis, rewatering restored water potential in the flag leaves, but the osmotic potential in the stem and flag leaf remained low longer. Osmotic adjustment was thus maintained longer after anthesis, showing that the plants invest more energy in the osmotic adjustment after anthesis than before anthesis. We hypothesize that this is because the plants consider the developing ear after anthesis a more important carbohydrate sink than the stem, which is a carbohydrate sink before anthesis, to be used later as a reserve. Low osmotic potential in the stem allowed turgor maintenance, while the low osmotic potential in the flag leaf led to an increase in leaf turgorbeyond the level of the control plants. This allowed leaf functioning under drought and assuredthat water was redirected to the flag leaf and not used to refill the stem storage.